Effect of fat source and fat combinations on starter pig performance - Thaler, R.C.; Allee, G.L.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two 5-wk trials utilizing a total of 324 weanling pigs (21 ± 3 d) were conducted to determine the effects of different fat sources and combinations on starter pig performance. Treatments consisted of a control (CONT) with no added fat and fat additions of either soybean oil (SOY), coconut oil (COCO), choice white grease (CWG), 1/2 SOY: 1/2 COCO (SOCO), or 1/2 CWG: 1/2 COCO (CWCO). Diets were supplemented with 10% fat for the first two wk of the study, and 5% fat for the next three wk. Daily feed intake (ADFI) was decreased for the first 2 wk when fat was added, but gains (ADG) and feed efficiency (F/G) were unaffected by dietary treatment. During the last 3 wk of the study, fat additions improved ADG and F/G. Also, pigs utilized CWCO diets more efficiently than CWG diets. For the overall 5 wk study, ADG and F/G were improved by fat additions. Within fat treatments, pigs gained faster on SOCO diets than on COCO diets and consumed more of the SOCO diets than either of the COCO or CWCO diets. Based on the results of this study, fat additions do enhance starter pig performance, with the soybean oil-coconut oil combination maximizing performance.
Keywords: Swine; Starter pig; Fat; Soybean oil; Coconut oil; Choice white grease